2015
DOI: 10.24925/turjaf.v3i6.356-360.265
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity and Phenolic Content of Apple Cider

Abstract: Fruit and vegetables are an important component of a healthy diet and the main antioxidant suppliers in the human diet. Consumption of foods derived from fruits and vegetables is also essential; fruit juices, ciders, wines, and vinegars also contain significant amounts of polyphenolic compounds. The aim of the study was to determine the effect maceration of antioxidant activity and phenolic content of apple cider. Red delicious apples were used to produce natural apple cider with and without inclusion of macer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 17 publications
2
12
3
Order By: Relevance
“…Relatively lower concentration of polyphenols in analyzed apple juice can be explained with polyphenol oxidase activity or their adsorption into the cell-wall matrix in the apple pomace during pressing (Nogueira et al 2008). Our results pointed out chlorogenic acid as the most abundant individual polyphenol compound in apple juice ranging from 38.53 to 140.66 mg L -1 what was in agreement with previous work by Budak et al (2015). Among other polyphenols, according to our results, procyanidin B2 and epicatechin can be singled out, in general representing together with other detected flavan-3-ol compounds more than 50% of total polyphenols in apple juices.…”
Section: Polyphenolic Composition Of Apple Juice and Winessupporting
confidence: 92%
See 2 more Smart Citations
“…Relatively lower concentration of polyphenols in analyzed apple juice can be explained with polyphenol oxidase activity or their adsorption into the cell-wall matrix in the apple pomace during pressing (Nogueira et al 2008). Our results pointed out chlorogenic acid as the most abundant individual polyphenol compound in apple juice ranging from 38.53 to 140.66 mg L -1 what was in agreement with previous work by Budak et al (2015). Among other polyphenols, according to our results, procyanidin B2 and epicatechin can be singled out, in general representing together with other detected flavan-3-ol compounds more than 50% of total polyphenols in apple juices.…”
Section: Polyphenolic Composition Of Apple Juice and Winessupporting
confidence: 92%
“…According to Nogueira et al (2008), low flavonols content may be an indicator of the poor extractability of the polyphenols from the peel during apple processing. Budak et al (2015) detected gallic acid only in apple juices which was not in agreement with our results. On the contrary, gallic acid was present in all wines ranging from 0.75 to 0.80 mg L -1 .…”
Section: Polyphenolic Composition Of Apple Juice and Winescontrasting
confidence: 91%
See 1 more Smart Citation
“…In addition, the radical scavenging ability of cider, especially the overripe cider, was significantly higher than in other cases. Budak et al 25 also reported high antioxidant activities in apple ciders compared to unfermented apple juice. The results showed that wax apple juice and its cider were more efficient in scavenging 2,2-diphenyl-1-picrylhydrazyl (DPPH) radicals and hydroxyl radicals than ABTS + radicals.…”
Section: Results and Discussionmentioning
confidence: 93%
“…However, in the recent years, much of the interest has developed in naturally occurring antioxidants, because of the adverse attention received by the synthetic antioxidants, and because of the worldwide trend to avoid or minimize the use of artificial food additives (Filiz and Seydim, 2014;Gad and Sayd, 2015;Saral et al, 2014). Also the use of natural antioxidants for frying purposes has increased during the last few years (Bera et al, 2006;Budak et al, 2015;Riveros et al, 2015;Urbancic et al, 2014). Plant extracts, especially antioxidants obtained from herbs and spices, have been proposed for stabilizing frying oils.…”
Section: Introductionmentioning
confidence: 99%